Kepribadian dan Emosi - Ansori, Aan (Jurnal Literasi Pendidikan Nusantara, 2020)
This paper is written with the aim of explaining the notion of personality and emotion, but in the discussion, it explains the emotional phenomenon symbolized in social media as information technology develops and almost everyone socializes using devices. The writing method uses Microsoft Word and journal templates. Mendeley's app is used for citation and APA 7th (American Psychological Association 7th edition) as reference style. The data for the discussion of papers are obtained from primary and secondary data from books and journals of international and national reputation. The results of writing this paper, personality and emotions are things that must be guarded wisely so as not to cause misunderstanding and offense in social media because it is influenced by several factors, including: social, educational level, age, gender, topic presented, areas with social status. , education levels, and different ages are very prone to misinterpretation / meaning. And it often happens in social media that it's easy to share symbols or images that don't necessarily know the meaning or meaning of these symbols or images, so gossip, ghibah and slander occur